1994
DOI: 10.1089/thy.1994.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer in Pregnant Women: Diagnostic and Therapeutic Management

Abstract: There is considerable literature on the effect of pregnancy on established thyroid cancer. In contrast, there are only isolated case reports of management of thyroid cancer diagnosed de novo during pregnancy. We describe four such patients. We recommend fine-needle aspiration biopsy (FNA) of solitary thyroid nodules found early in pregnancy. When the cytopathology is diagnostic of thyroid cancer, thyroidectomy under local or general anesthesia is advised. The patient should be given levothyroxine in a dose suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Level I-USPSTF Fine-needle aspiration. FNA is a safe diagnostic tool in pregnancy and may be performed in any trimester (229,(234)(235)(236)(237)(238)(239)(240)(241)(242). Two retrospective case series of FNAs performed during pregnancy, involving a total of 94 patients, have been…”
Section: And Recommendation 46mentioning
confidence: 99%
“…Level I-USPSTF Fine-needle aspiration. FNA is a safe diagnostic tool in pregnancy and may be performed in any trimester (229,(234)(235)(236)(237)(238)(239)(240)(241)(242). Two retrospective case series of FNAs performed during pregnancy, involving a total of 94 patients, have been…”
Section: And Recommendation 46mentioning
confidence: 99%
“…Probably the report from 1976 by Asteris and DeGroot (29) is the only one to state that pregnancy should be avoided by women with known residual thyroid cancer, and that therapeutic abortion should be considered in such a circumstance. More recent studies have concluded that "differentiated thyroid cancer should not inhibit a patient from having a child, and in general it should not be a reason for recommending therapeutic abortion" (30).…”
Section: Discussionmentioning
confidence: 99%
“…The Stanford group (30) also feel that it is important to differentiate between the nodule found early in pregnancy and the one found later. They feel that "it would not be desirable to wait for [8][9][10][11][12] months with anxiety in the case of nodules found early in pregnancy, but it would be tolerable to wait for 2-4 months before work-up or surgery in cases of nodules found later in pregnancy" (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal timing of treatment, however, is still controversial, with some authors advocating surgery during the midtrimester whilst others recommend waiting until after delivery (3)(4)(5). We reviewed the records of pregnant women with thyroid cancer treated in our unit with particular regard to timing of treatment and outcome.…”
Section: Introductionmentioning
confidence: 99%